References Appeared in the Articles Published in IASLIC Bulletin (2010-2012): A Study of Recency - Sardar, Nikhil Kumar (Journal of Information and Knowledge, 2014)
The aim of this paper is to study recency, weighted recency and Average Rated Recency of the cited items in the articles published in IASLIC Bulletin during the period from 2010 to 2012 using statistical methods.